Unique mutational profile associated with a loss of TDG expression in the rectal cancer of a patient with a constitutional PMS2 deficiency - Vasovcak, P; Krepelova, A; Menigatti, M; Puchmajerova, A; Skapa, P; Augustinakova, A; Amann, G; Wernstedt, A; Jiricny, J; Marra, G; Wimmer, K (DNA repair, 2012)
Cells with DNA repair defects have increased genomic instability and are more likely to acquire secondary mutations that bring about cellular transformation. We describe the frequency and spectrum of somatic mutations involving several tumor suppressor genes in the rectal carcinoma of a 13-year-old girl harboring biallelic, germline mutations in the DNA mismatch repair gene PMS2. Apart from microsatellite instability, the tumor DNA contained a number of C:G→T:A or G:C→A:T transitions in CpG dinucleotides, which often result through spontaneous deamination of cytosine or 5-methylcytosine. Four DNA glycosylases, UNG2, SMUG1, MBD4 and TDG, are involved in the repair of these deamination events. We identified a heterozygous missense mutation in TDG, which was associated with TDG protein loss in the tumor. The CpGs mutated in this patient's tumor are generally methylated in normal colonic mucosa. Thus, it is highly likely that loss of TDG contributed to the supermutator phenotype and that most of the point mutations were caused by deamination of 5-methylcytosine to thymine, which remained uncorrected owing to the TDG deficiency. This case provides the first in vivo evidence of the key role of TDG in protecting the human genome against the deleterious effects of 5-methylcytosine deamination.
Keywords: Molecular Sequence Data; DNA-Binding Proteins; sekvence aminokyselin; DNA Repair Enzymes; Homozygote; mismatch repair endonukleáza PMS2; Heterozygote; mladiství; fenotyp; Thymine DNA Glycosylase; enzymy opravy DNA; Phenotype; ženské pohlaví; nádory rekta; adenosintrifosfatasy; Mismatch Repair Endonuclease PMS2; Humans; Amino Acid Sequence; thymin-DNA-glykosylasa; homozygot; DNA vazebné proteiny; Adenosine Triphosphatases; Rectal Neoplasms; molekulární sekvence - údaje; zárodečné mutace; Female; Germ-Line Mutation; Adolescent; lidé; heterozygot